2014
DOI: 10.1073/pnas.1404219111
|View full text |Cite|
|
Sign up to set email alerts
|

Kaposi's sarcoma-associated herpesvirus LANA recruits the DNA polymerase clamp loader to mediate efficient replication and virus persistence

Abstract: Significance Kaposi's sarcoma herpesvirus (KSHV) latently infects tumor cells, and viral episomal DNA replicates once each cell cycle. KSHV does not express DNA replication proteins during latency. Instead, KSHV latency-associated nuclear antigen (LANA) recruits host cell DNA replication machinery to the replication origin. However, the mechanism by which LANA mediates replication is uncertain. Here, we show LANA recruits replication factor C, the DNA polymerase clamp [proliferating cell nuclear anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…Both of these complexes have been shown to directly interact with LANA and to facilitate latent viral replication (33)(34)(35). Hypothesizing that LANA spirals may be induced in trans, the initiation sites for latent KSHV replication would not necessarily have to be restricted to the TR region.…”
Section: The Lana Dbd Exhibits Two Dna-binding Modesmentioning
confidence: 99%
“…Both of these complexes have been shown to directly interact with LANA and to facilitate latent viral replication (33)(34)(35). Hypothesizing that LANA spirals may be induced in trans, the initiation sites for latent KSHV replication would not necessarily have to be restricted to the TR region.…”
Section: The Lana Dbd Exhibits Two Dna-binding Modesmentioning
confidence: 99%
“…Replication factor C, the DNA polymerase clamp (proliferating cell nuclear antigen (PCNA)) loader allows processive DNA replication and is recruited to TR DNA by direct interaction with LANA to mediate replication. However, LANA residues 262-320, rather than the C-terminal domain, are critical for replication factor C interaction (63). Topoisomerase II␤, which facilitates DNA replication by inducing double stranded breaks, interacts with LANA N-terminal amino acids 1-32 and not the C-terminal domain (64).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic profiling of EBV EBNA1 by AP-LC-MS/MS defined protein interactions in EBV-associated cancers in both latent and lytic infection (56). Similar studies using KSHV LANA, showed that the RFC complex interacted with LANA and is important for viral replication (57). Another study defined cellular proteins that interacted with LANA, and determined which of these interactions were mediated through the LANA SUMO Interacting motif (SIM) (58).…”
Section: Molecular and Cellular Proteomics 16 Supplement 4 S67mentioning
confidence: 93%